Katherine Anne Porter papers - Porter, Katherine Anne, 1890-1980.
Chiefly correspondence from Porter to Marcelle Sibon, Porter's French translator, along with other papers relating to Porter's writings, her observations on the work of fellow authors and poets, general literary topics, and personal affairs. Subjects include Porter's early life in Texas, her political beliefs, current events, and world affairs. Other correspondents include Gerald Ashford and Louise Y. (Mrs. Thomas F.) Gossett.
Journalist, author, and political activist.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Ashford, Gerald, -- 1907- -- Correspondence; Gossett, Louise Y. -- Correspondence; Porter, Katherine Anne, -- 1890-1980 -- Political and social views; Sibon, Marcelle -- Correspondence; History, Modern -- 20th century; Literature; Poetry; Texas -- Social life and customs; United States -- History -- 20th century; Authors; Journalists; Political activists